PENGARUH RATA LAMA SEKOLAH, PENGELUARAN PERKAPITA, PENDAPATAN ASLI DAERAH, INVESTASI, TINGKAT PENGANGGURAN TERBUKA TERHADAP TINGKAT KEMISKINAN DI NUSA TENGGARA BARAT TAHUN 2012-2021 - Nizar, Fauzan; Arif, Muhammad (KOMITMEN: Jurnal Ilmiah Manajemen, 2023)
This study aims to determine the effect of the average length of schooling, per capita expenditure, local revenue, investment, open unemployment rate on the poverty rate in all districts and cities of West Nusa Tenggara Province. The data used is secondary data sourced from the Central Bureau of Statistics, West Nusa Tenggara, the Central Bureau of Statistics of Riau Province and the Regional Development Planning Agency of Riau Province. The secondary data used is Panel data for 2012-2021 by Regency/City in West Nusa Tenggara Province. Data analysis using panel data regression.